2021
DOI: 10.1038/s41598-021-98053-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early and intermediate biomarkers for ARDS mortality by multi-omic approaches

Abstract: The lack of successful clinical trials in acute respiratory distress syndrome (ARDS) has highlighted the unmet need for biomarkers predicting ARDS mortality and for novel therapeutics to reduce ARDS mortality. We utilized a systems biology multi-“omics” approach to identify predictive biomarkers for ARDS mortality. Integrating analyses were designed to differentiate ARDS non-survivors and survivors (568 subjects, 27% overall 28-day mortality) using datasets derived from multiple ‘omics’ studies in a multi-inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…These 40 studies produced 44 unique gene lists (22 transcriptomic, 13 proteomic, and 9 based on genome-wide association studies (GWAS); see Table 1). Three studies reported results from multiple methodologies 33,38,44 , and several used more than one tissue type 18,21,32 . Excluding GWAS, 14 gene lists (40%) were derived from lung or airways samples, and 21 (60%) from blood.…”
Section: Resultsmentioning
confidence: 99%
“…These 40 studies produced 44 unique gene lists (22 transcriptomic, 13 proteomic, and 9 based on genome-wide association studies (GWAS); see Table 1). Three studies reported results from multiple methodologies 33,38,44 , and several used more than one tissue type 18,21,32 . Excluding GWAS, 14 gene lists (40%) were derived from lung or airways samples, and 21 (60%) from blood.…”
Section: Resultsmentioning
confidence: 99%
“…Early detection of the patients at risk for ARDS remains of paramount importance, since it is associated with relevant mortality rates of 30–40% 34 . Given the multitude of stimuli and their heterogeneity, that may contribute to the onset of ARDS, the need of biomarkers as an extension of clinical scores for the prediction of ARDS-related mortality has been highlighted in the literature 35 , 36 . Johnsson et al recently reported a significant elevation of bio-ADM levels at the time of admission in ICU in patients that were diagnosed with ARDS within 72 h after admission 37 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, HDACs repress the production of proinflammatory cytokines in alveolar macrophages in chronic inflammatory lung conditions such as chronic obstructive pulmonary disease (44,45). HDAC class I and chromatin modifying enzymes were identified as top pathways associated with ARDS mortality in a study using a multi-omics approach with multiple publicly available datasets (46). DNA methylation is another epigenetic modification that emerged in the Reactome analysis that distinguished moderate/ severe from mild pediatric ARDS.…”
Section: Discussionmentioning
confidence: 99%